Development of a Novel Immune-Related Gene Signature to Predict Prognosis and Immunotherapeutic Efficiency in Gastric Cancer - Liu, Dongliang; Xu, Yuanmin; Fang, Yu; Hu, Kongwang (Frontiers in Genetics, 2022)
Abstract Background: Gastric cancer (GC) is the fifth most common cancer and the third leading cause cancer-related deaths globally. Herein, we attempted to develop a novel immune-related gene signature that could predict the prognosis and immunotherapeutic efficiency for GC patients. Methods: The mRNA transcription data and corresponding clinical data of GC were downloaded from The Cancer Genome Atlas (TCGA) database as the training group and GSE84433 dataset as the testing cohort, followed by acquisition of immune-related genes from the InnateDB resource and ImmPort database. Using the univariate Cox regression analysis, an immune-related gene signature was developed. Several immunogenomic analyses were performed to illustrate the associations between the immune risk score and tumor mutational burden, immune cell infiltrations, function of immune infiltration, clinical characteristics, immune subtype and immunotherapeutic response. Results: The analysis of 343 GC samples and 30 normal samples from the TCGA database gave rise to 8713 immune-related genes (DEGs) and 513 differentially expressed immune-related genes (DEIRGs) were extracted. The novel immune-related gene signature contained eight DEIRGs (FABP4, PI15, RNASE2, CGB5, INHBE, RLN2, DUSP1 and CD36) and was found can serve as an independent predictive and prognostic factor for GC. Then, the GC patients were separated into the high- and low-risk groups based on the median risk score, wherein the low-risk group presented better prognosis and was more sensitive to immunotherapy than the high-risk group. According to the time-dependent ROC curves and AUCs, the immunotherapeutic value of the signature was better than that of the TIDE score and TIS score. In addition, the AUCs of the risk score for predicting 1-, 2-, and 3-year OS were 0.675, 0.682, and 0.710, which indicated that the signature had great predictive power. Conclusion: This study presents a novel immune-related gene signature based on the tumor immune microenvironment, which could improve the prediction of the prognosis and immunotherapeutic efficiency for GC patients. The powerful signature may serve as novel biomarkers and provide therapeutic targets for precision oncology in clinical practice.